Small size boundary effects on two-pion interferometry - Zhang, Q. H.; Padula, Sandra S. (American Physical Society (APS), 2000)
Bose-Einstein correlations of two identically charged pions are derived when these particles, the most abundantly produced in relativistic heavy-ion collisions, are confined in finite volumes. Boundary effects on a single-pion spectrum are also studied. Numerical results emphasize that the conventional formulation usually adopted to describe two-pion interferometry should not be used when the source size is small, since this is the most sensitive case to boundary effects. Specific examples are considered for better illustration.